2019
DOI: 10.21608/jfds.2019.61875
|View full text |Cite
|
Sign up to set email alerts
|

Mahmoud, A. M.1; E. A. Ali1; Manal A. M. Hassan2* and Asmaa S. A. Sayed1 1 Department of Agronomy, Faculty of Agriculture, Assiut University, Assiut, 71526, Egypt 2 Food Science and Technology Department, Faculty of Agriculture, Assiut University, Assiut 71526, Egypt

Abstract: designed BPF are as follows: W 1 5 1.5 mm, W 2 5 1.0 mm, W 3 5 0.6 mm, W 4 5 1.0 mm, W 5 5 0.88 mm, L 1 5 5.7 mm, L 2 5 5.88 mm, L 3 5 9.23 mm, L 4 5 11.0 mm, L 5 5 12.0 mm, L 6 5 3.51 mm, d 1 5 0.17 mm, d 2 5 0.17 mm, d 3 5 0.17 mm, and d 4 5 0.17 mm.ABSTRACT: In this article, an ultrawideband (UWB) antenna with triple band-rejection characteristics is proposed. The antenna is compact with size of 22.5 3 24 mm 2 . Matching between a sector-disk shaped radiating patch and the 50-X microstrip line is manipulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 108 publications
1
10
0
Order By: Relevance
“…These results indicated that the essential oils at both concentrations inhibited the growth of coliform group bacteria. These results are similar as mentioned by (Mahmoud, 2013) who observed that coliform group disappear during cold storage in most minced beef samples treated with essential oils. (Mahmoud, 2022) reported that the coliform group disappear in turkey meatballs samples treated with thyme essential oil after 12 days.…”
Section: Changes In Psychrotrophic Bacterial Count Of Chilled Minced ...supporting
confidence: 92%
“…These results indicated that the essential oils at both concentrations inhibited the growth of coliform group bacteria. These results are similar as mentioned by (Mahmoud, 2013) who observed that coliform group disappear during cold storage in most minced beef samples treated with essential oils. (Mahmoud, 2022) reported that the coliform group disappear in turkey meatballs samples treated with thyme essential oil after 12 days.…”
Section: Changes In Psychrotrophic Bacterial Count Of Chilled Minced ...supporting
confidence: 92%
“…Obviously, the highest values of fixed oil % were given by utilizing filter mud at the high level (210 g/plant) which augmented it by 6.2 and by 5.7% over unfertilized ones, during the two growing seasons, respectively. The augment in fixed oil as a result of applying organic manures have to be proved by Маnјunatha et al (2009), Kalkhoran et al (2013), andRasool et al (2015) on sunflower, and on roselle (Ahmed et al, 1998;Mahmoud, 2022). In respect to biofertilization treatments, data in Table ( 6) emphasized that fixed oil % of borage was significantly affected by the inoculation with the three studied microorganisms, during the two consecutive seasons.…”
Section: Fixed Oil Percentagementioning
confidence: 88%
“…The increments in herb weight, flower weight and seed yield due to using organic manures which have been studied by El Houssini (2009), Fouad (2017), Awad (2019) on borage plants. An augment in fixed oil and alkaloids content on borage (Fouad 2017), elevate in oil content of sunflower (Kalkhoran et al, 2013;Маnјunatha et al, 2009;Rasool et al 2015), increase in alkaloids content of periwinkle (Hassan, 2012) and on tobacco (Kurt and Ayan, 2014), as well as augment in fixed oil of roselle (Ahmed et al, 1998;Mahmoud, 2022), resulting from adding organic manures. Using bio-fertilizers (useful microorganisms) led to enhance soil fertility by elevating the number of microorganisms and accelerate certain microbial processes in rhizosphere zone.…”
Section: Introductionmentioning
confidence: 99%
“…The El-Barramiya area has been studied by many researchers in order to identify subsurface structures, such as faults, shear zones, and lithological contacts, which may affect ore deposit mineralization and allow effective prospecting via a range of geological and geophysical techniques (Mahmoud et al, 2013;Saleh et al, 2018;Mohamed et al, 2022;Abdelrady et al, 2023). Here, we present the results of eld work, petrography, uid inclusion analysis, and geochemical analyses of mineralized rocks (listvenites, and gold-bearing quartz and carbonate veins) in the El-Barramiya area.…”
Section: Introductionmentioning
confidence: 99%